Sankofa - Amenyedzi, Seyram B.; Maton, Yosi Apollos; Yele, Marceline L. (2024)
BiAS 39 is an essay collection on women’s Liberation Theology in West Africa, issued as one of three regional volumes commissioned in preparation of the Circle of Concerned African Women Theologians’ (CIRCLE) return to Ghana, its place of birth, after 35 years. The volumes rose within the context of preparing the meeting in July 2024 by remembering the founding members of the CIRCLE. The three regional volumes focus on exploring South (BiAS 41), East/Central (BiAS 40) and West African (BiAS 39) womanist/feminist Liberation Theology generated since the launch of the CIRCLE in 1989. The contributions on the lives and works of groundbreaking African women in the Theology of Liberation constitute an international, interreligious, and interdisciplinary compendium for redemptive theological research. The book is dedicated to Rabiatu Deinyo Ammah, the first Muslim woman in the CIRCLE and one its founding matriarchs.